2021
DOI: 10.3390/biom11060878
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Stem Cells Secretome and Its Potential Application in “Stem Cell-Free Therapy”

Abstract: Adipose-derived stem cells (ASCs) secrete many cytokines, proteins, growth factors, and extracellular vesicles with beneficial outcomes that can be used in regenerative medicine. It has great potential, and the development of new treatment strategies using the ASCs secretome is of global interest. Besides cytokines, proteins, and growth factors, the therapeutic effect of secretome is hidden in non-coding RNAs such as miR-21, miR-24, and miR-26 carried via exosomes secreted by adequate cells. The whole secretom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
108
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(108 citation statements)
references
References 180 publications
(241 reference statements)
0
108
0
Order By: Relevance
“…The research related to the use of MSCs in the treatment of difficult-to-heal wounds has evolved over the years, starting with autologous cell transplants [17], transplantation of cells embedded in hydrogels [18,19], through the delivery of a MSC secretome as a whole [3] or isolated exosomes [20,21]. The latest trends in research on cell-free therapy focus on the use of MSC-produced bioactive factors in combination with hydrogel carriers.…”
Section: Discussionmentioning
confidence: 99%
“…The research related to the use of MSCs in the treatment of difficult-to-heal wounds has evolved over the years, starting with autologous cell transplants [17], transplantation of cells embedded in hydrogels [18,19], through the delivery of a MSC secretome as a whole [3] or isolated exosomes [20,21]. The latest trends in research on cell-free therapy focus on the use of MSC-produced bioactive factors in combination with hydrogel carriers.…”
Section: Discussionmentioning
confidence: 99%
“…As important carriers of signaling molecules in intercellular communication, exosomes are being developed as potential therapeutic agents or prognostic biomarkers in multiple disease models [ 12 , 13 ]. Previous studies have demonstrated that ADSC-Exos can be used for wound healing, atopic dermatitis, cardiovascular, inflammatory, and autoimmune diseases [ 14 ]. It has been shown that DP spheroid-derived exosomal miR-218-5p can promote hair regeneration and upregulate the β -catenin signaling pathway [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…ASCs secrete numerous soluble mediators, inflammatory cytokines, angiogenic, trophic and growth factors such as vascular endothelial growth factor (VEGF), hepatocyte growth factor (HGF), brain-derived neurotrophic factor (BDNF), insulin-like growth factor (IGF), basic fibroblast growth factor (bFGF), transforming growth factor beta 1 (TGF-β1), stromal cell-derived factor (SDF)-1α, and interleukins. The paracrine factors secreted by ASCs contribute to tissue repair, wound healing and organ regeneration ( Kapur and Katz, 2013 ; Suga et al, 2014 ; Brini et al, 2017 ; Li et al, 2019 ; Trzyna and Banaś-Ząbczyk, 2021 ). Studies have also shown that ASCs-EVs stimulate the regeneration of damaged tissue similar to the ASCs ( Hu et al, 2016 ; Qiu et al, 2018 ).…”
Section: Application Of Ascs For Regenerative Medicinementioning
confidence: 99%
“…ASCs and ASC-derived extracellular vesicles (ASC-EVs) and ASC conditioned media (ASCs-CM) have been extensively studied and widely used in regenerative medicine. Studies have shown the effectiveness of ASCs and ASCs secretome ( Zuk et al, 2001 ; Giannasi et al, 2020 ; Trzyna and Banaś-Ząbczyk, 2021 ) therapy in numerous diseases such as cardiovascular, bone regeneration, osteoarthritis graft versus host disease (GvHD) and autoimmune disorders such Crohn’s diseases ( Galindo et al, 2017 ), systemic lupus erythematosus (SLE) and multiple sclerosis ( Maria et al, 2017 ; Al-Ghadban and Bunnell, 2020 ). In addition, researchers have recently been designing new 3D biomaterials by combining ASCs with biomimetic scaffolds composed of either natural or synthetic materials.…”
Section: Introductionmentioning
confidence: 99%